Bilastine for the treatment of urticaria. (August 2013) - Jáuregui, Ignacio; Ferrer, Marta; Bartra, Joan; del Cuvillo, Alfonso; Dávila, Ignacio; Montoro, Javier; Mullol, Joaquim; Sastre, Joaquín; Valero, Antonio
Abstract : Introduction: Urticaria is a highly prevalent disease among people. First-choice treatment continues to be centred on the second-generation H1 antihistamines, including a wide group of drugs with a better therapeutic index (or risk:benefit ratio) than the classic ones, even in the high, off-label dosage occasionally required in chronic urticaria.Bilastine is a newly registered H1-antihistamine for treatment of allergic rhinoconjunctivitis and urticaria. With established antihistaminic and antiallergic properties, it is widely reviewed in the medical literature; however, to our knowledge, a specific review of bilastine's role in the treatment of urticaria was lacking. Areas covered: This article reviews the medical literature on the effectiveness and safety of bilastine in urticarial syndromes, either spontaneous or inducible, by means of a Medline search from 1990 to present, completed with some nonpublished data provided by the manufacturer. Expert opinion: Once-daily treatment with bilastine 20 mg is effective in managing symptoms and improving patient's quality of life in chronic urticaria, with at least comparable efficacy to levocetirizine. As far as studies in healthy volunteers, clinical assays, and recent clinical experience can establish, bilastine's safety profile is adequate, appearing to be entirely free from cardiovascular effects, and not impairing psychomotor performance or actual driving, even at twice the therapeutic dose.